Hukuman Mati Menurut Undang-Undang Nomor 1 Tahun 2023 Tentang KitabUndang-Undang Hukum Pidana Dalam Perspektif Hak Asasi Manusia - Daffa Rizky Dewanto; Rahtami Susanti (Wijayakusuma Law Review, 2023)
Indonesia is a country that acknowledges the existence of Human Rights, but this does not lead to the abolishmentof the death penalty in its positive law. Both the old and new Criminal Codes (KUHP) still regulate the deathpenalty, albeit in different concepts. This research aims to identify the differences between the death penalty in theold and new Criminal Codes and to understand and analyze the death penalty in the new Criminal Code from ahuman rights perspective. The research employs a normative juridical method. The findings indicate that thedeath penalty in the new Criminal Code is no longer the primary punishment as in old Criminal Codes and has beenreplaced with an alternative penalty. Under the new Criminal Code, those sentenced to death will undergo aprobationary period of 10 (ten) years, and if they demonstrate good behavior during this period, the death penaltywill be commuted to life imprisonment or imprisonment for 20 (twenty) years. This change is motivated by theperception that the death penalty constitutes a violation of human rights.